Comparison of metabolic and inflammatory outcomes in women who used oral contraceptives and the levonorgestrel-releasing intrauterine device in a general population. - Morin-Papunen, L; Martikainen, H; McCarthy, M; Franks, S; Sovio, U; Hartikainen, A; Ruokonen, A; Leinonen, M; Laitinen, J; Järvelin, MR; Pouta, A (2008)
OBJECTIVE: We compared the metabolic and cardiovascular parameters of a reference group of women with those of women who used 2 contraceptive regimes that are used worldwide: the levonorgestrel-releasing intrauterine device and oral contraceptives. STUDY DESIGN: We investigated a cohort of 2814 women at age 31 years from the general population-based Northern Finland Birth Cohort who were born in 1966. Women were classified as oral contraceptive users (n = 687 women), levonorgestrel-releasing intrauterine device users (n = 168 women), or no use of hormonal contraception (reference group; n = 1959 women). The analyses were adjusted for body mass index, current alcohol use, household income, and area of residence. RESULTS: Compared with the reference group, oral contraceptive users had higher systolic and diastolic blood pressure, raised levels of inflammatory indices (C-reactive protein), and impaired insulin sensitivity. Levonorgestrel-releasing intrauterine device users displayed a lower high-density lipoprotein and total cholesterol, but a similar cholesterol/ high-density lipoprotein ratio, and higher leukocyte count compared with the reference group. Oral contraception users were insulin-resistant compared with levonorgestrel-releasing intrauterine device users with higher blood pressure, raised lipid levels (such as total cholesterol and triglycerides) and insulin levels, and lower homeostasis model assessment and insulin sensitivity, despite smaller waist and lower waist-hip ratio. CONCLUSION: Oral contraception usage was associated with adverse findings in several metabolic, cardiovascular, and inflammatory parameters, which is consistent with an increased future risk of cardiovascular and metabolic disease. These findings should invite more criticism of recent trends that encourage the prescription of oral contraceptives for years during reproductive life and especially in premenopausal women. In contrast, levonorgestrel-releasing intrauterine device or progestin-only pills may offer long-term health benefits over oral contraceptives and should be preferred to oral contraceptives for women in their forties and/or with metabolic risk factors for cardiovascular diseases and type 2 diabetes mellitus.